Nursing care for postpartum women at home under the perspective of the carraro care model - Mariely Carmelina Bernardi Fornari; Telma Elisa Carraro; Ariane Thaise Frello Roque; Aline Massaroli (Universidade Federal de Santa Maria, 2016)
Aim: to present the journeys of the nursing home-care for women during immediate and later post-partum periods given the perspective of the Carraro Care Model. Methodology: convergent-care study developed in the town of Corbélia - Paraná, from April to June 2011. Results: care strategies directed to a single care and towards unique human beings emerged. Therefore, caution, flexibility, interest and to act reflexibly with the woman are important matters to exercise nursing in a way that values its science and art. Conclusion: with Carraro Care Model, it is possible to awake the Vital Power of postpartum women and their families for a dynamic care, that values the biographical relational context, where the internal and external environment are linked to interpersonal relationships.